Uses Of Communicative And Collaborative Activities In E-Learning: Moodle Platform As A Model/ Ø§Ø³ØªØ®Ø¯Ø§Ù…Ø§Øª Ø§Ù„Ø£Ù†Ø´Ø·Ø© Ø§Ù„ØªÙˆØ§ØµÙ„ÙŠØ© ÙˆØ§Ù„ØªØ¹Ø§ÙˆÙ†ÙŠØ© ÙÙŠ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø§Ù„ÙƒØªØ±ÙˆÙ†ÙŠ: Ù…Ù†ØµØ© Moodle Ù†Ù…ÙˆØ°Ø¬Ø§ - Bendridi, Abdelghani (Ijaz Arabi Journal of Arabic Learning, 2021)
This study aims to defining the uses of communicative and collaborative activities in learning process via Moodle platform, through a descriptive research. This platform is a kind of the learning management systems (LMS), it is specially designed to manage interactive electronic lessons, with the aim of supporting the learning process, whether hybrid learning (in Classroom and via platform) or completely virtual learning. In this research, we will focus on the most important uses and features it provides, as well as the contribution of the educational activities to creating new tools of communication between students and teachers and how to make learning process more interactive than classroom courses, so we describe and analyze in this study the most useful educational activities in Moodle platform (forum, chat, wiki, glossary, survey and database) and the different uses through the examples that we created.The most important results of this study are: The E-learning platforms Moodle provided an environment for active learning through communicative and collaborative activities that simulate the Learning process in the classroom. Indeed, these activities made it easier for teachers to follow the learners better than what is available in the classroom, and enabled their learning to be assessed better. Therefore, the challenge is how to design educational activities for achieving the objectives of the lessons in E-learning platforms.